A Political Ecology of Resistance: Actions and Reactions of Agrarian Socio-territorial Movements in Latin America - Moura, Joana Tereza Vaz de; Cavalcante, Leandro Vieira; Jara, Cristian Emanuel; Saettone, Julieta; Fernandes, Bernardo Mancano [UNESP]; Villalba, Ana Eliza; Bitencourt, Silmara Olveira Moreira [UNESP]; Bolanez, Claurdia Yesica Fonzo (Sage Publications Inc, 2024)
Territorial disputes have intensified in Latin America due to the advance of neo-extractivism, while agrarian socio-territorial movements have created strategies of resistance and reinvention of their territorialities. In dialogue with political ecology perspectives, we seek to understand the dynamics of these movements in Argentina and Brazil. We analyzed the information systematized in the DataLuta Network database on the actions and reactions of socio-territorial movements based on published news reports in 2021. We noted that, even with different political contexts, the socio-territorial movements of Argentina and Brazil have included environmental issues in their agendas, demonstrated by their commitment to the fight against pesticides, agro-industry, and mining, and in defense of agroecology and the production of healthy food.La disputa territorial se ha intensificado en America Latina por el avance del neoextractivismo, mientras que los movimientos socioterritoriales agrarios han creado estrategias de resistencia y reinvencion de sus territorialidades. Dialogando con las perspectivas de la ecologia politica, buscamos comprender la dinamica de estos movimientos en Argentina y Brasil. Analizamos la informacion sistematizada en la base de datos de la Red DataLuta sobre las acciones y reacciones de los movimientos socioterritoriales a partir de las noticias publicadas en 2021. Notamos que, aun con diferentes contextos politicos, los movimientos socioterritoriales de Argentina y Brasil han incluido la cuestion ambiental en sus agendas, que se manifiesta en su compromiso con la lucha contra los plaguicidas, la agroindustria y la mineria, en la defensa de la agroecologia y la produccion de alimentos saludables.
Keywords: Socio-territorial movements; Political ecology; Agroecology; Reforestation